2021
DOI: 10.3390/cancers13102429
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation Dictates the Cancer Immune Environment in Pancreatic Ductal Adenocarcinoma and Other Adenocarcinomas

Abstract: Generally, patients with pancreatic ductal adenocarcinoma, especially those with wide metastatic lesions, have a poor prognosis. Recently, a breakthrough in improving their survival has been achieved by using first-line chemotherapy, such as gemcitabine plus nab-paclitaxel or oxaliplatin plus irinotecan plus 5-fluorouracil plus calcium folinate. Unfortunately, regimens with high effectiveness are still absent in second- or later-line settings. In addition, although immunotherapy using checkpoint inhibitors def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…The relationship between the immune system and pancreatic cancer development is complex. Pancreatic inflammation, including immune cell infiltration associated with pancreatitis, can promote the initiation of pancreatic cancer lesion formation [39,49], while subsequent growth and progression of Kras G12D -driven pancreatic cancer are supported by the recruitment of immune cells that generate a permissive, immunosuppressive tumor microenvironment [50][51][52]. Therefore, we assessed the effect of loss of Prkci expression on infiltrating immune cells in Kras G12D -driven dysplastic pancreatic lesions.…”
Section: Ablation Of Pancreatic Prkci Promoted Panin Formation But Bl...mentioning
confidence: 99%
“…The relationship between the immune system and pancreatic cancer development is complex. Pancreatic inflammation, including immune cell infiltration associated with pancreatitis, can promote the initiation of pancreatic cancer lesion formation [39,49], while subsequent growth and progression of Kras G12D -driven pancreatic cancer are supported by the recruitment of immune cells that generate a permissive, immunosuppressive tumor microenvironment [50][51][52]. Therefore, we assessed the effect of loss of Prkci expression on infiltrating immune cells in Kras G12D -driven dysplastic pancreatic lesions.…”
Section: Ablation Of Pancreatic Prkci Promoted Panin Formation But Bl...mentioning
confidence: 99%
“…MutKRAS cancer cells orchestrate a pro-tumorigenic microenvironment [14][15][16][17]27]. Though, whether and how tumor microenvironment-derived signals affect mutKRAS signaling and the subsequent impact on cancer cells response has been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mutKRAS on the regulation of the tumor immune microenvironment is one of the most well described noncancer cell effect. Specifically, mutKRAS immunomodulator effects, have been reported to occur at the level of recruitment, activation, and differentiation of immune cells, supporting the immune compartment protumorigenic roles, and cancer cell evasion from immunosurveillance [6][7][8][9][10][11]13 . The effects of mutKRAS on the modulation of fibroblasts and cancer associated fibroblasts (CAFs) phenotypes are not so well studied and the majority of the available studies are focused on pancreatic cancer 6,7 .…”
Section: Introductionmentioning
confidence: 93%
“…Adding to the roll of key cancer activities controlled by mutKRAS, it has been shown that its oncogenic signaling extends beyond the cancer cell to orchestrate a pro -tumorigenic microenvironment [6][7][8][9][10][11] . Within the tumor microenvironment (TME), immune cells and fibroblasts are amongst the most commomly cell types found 6,12 .…”
Section: Introductionmentioning
confidence: 99%